Managing dyspraxia: Pre-school teachers' perceptions, experiences and strategies. Issue 2 (4th March 2019) - Pedro, Athena; Goldschmidt, Tessa
Abstract : Dyspraxia is a childhood developmental disorder that manifests as a difficulty in thinking, planning, and executing planned movements or tasks. Dyspraxia affects approximately 5–6% of school-aged children. This study aimed to explore pre-school teachers' awareness and understanding of dyspraxia, and the support they desire for teaching children with dyspraxia. Informants were 15 pre-school teachers from the Cape Peninsula, South Africa (black = 1; coloured/mixed race = 13; white = 1). The teachers completed semi-structured interviews regarding their awareness and knowledge of dyspraxia and the support they require to better facilitate the learners' development. A thematic analysis of the data suggested that the teachers were aware of the behavioural and cognitive difficulties associated with dyspraxia and that they need to seek professional development to enhance their management of children with dyspraxia. Early intervention strategies, in partnership with the parent carers of the children, appear to hold good prospects for the successful management of dyspraxia among school-aged children.